2016
DOI: 10.1016/j.soilbio.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Iron addition to soil specifically stabilized lignin

Abstract: a b s t r a c tThe importance of lignin as a recalcitrant constituent of soil organic matter (SOM) remains contested. Associations with iron (Fe) oxides have been proposed to specifically protect lignin from decomposition, but impacts of Fe-lignin interactions on mineralization rates remain unclear. Oxygen (O 2 ) fluctuations characteristic of humid tropical soils drive reductive Fe dissolution and precipitation, facilitating multiple types of Fe-lignin interactions that could variably decompose or protect lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 31 publications
8
42
0
Order By: Relevance
“…It is observed that up to an average of 40% of lignin phenols are ‘protected’ by reactive Fe in the subsoils and not detected by the conventional CuO oxidation method. More importantly, in line with previous findings2029, wetland WTD not only decreases phenol oxidative activity and β-1,4-glucosidase (β-glucosidase) activity but also increases Fe-bound lignin phenols in the air-exposed soils due to Fe(II) oxidation. We hence propose that redox-induced Fe transformation may act as an ‘iron gate’ against the ‘enzyme latch’ in regulating SOC dynamics under oxygen exposure during wetland WTD.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…It is observed that up to an average of 40% of lignin phenols are ‘protected’ by reactive Fe in the subsoils and not detected by the conventional CuO oxidation method. More importantly, in line with previous findings2029, wetland WTD not only decreases phenol oxidative activity and β-1,4-glucosidase (β-glucosidase) activity but also increases Fe-bound lignin phenols in the air-exposed soils due to Fe(II) oxidation. We hence propose that redox-induced Fe transformation may act as an ‘iron gate’ against the ‘enzyme latch’ in regulating SOC dynamics under oxygen exposure during wetland WTD.…”
supporting
confidence: 90%
“…The observed increase of Fe-bound lignin phenols in the air-exposed soil layers echoes lignin stabilization with the oxidation of added Fe(II) into a moist tropical soil29. Since none of the extractable Fe increased under WTD (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 70%
“…However, Feo was more significantly positively correlated with the intensity of aromatic C (R 2 = 0.8497, P < 0.001) than with that of O-alkyl C, indicating that Feo may preferentially preserve aromatic organic compounds. This finding agrees with the results of Hall et al (2016), who conducted an incubation experiment with and without Fe addition to the soil and found that the precipitation of reactive Fe oxides following Fe (II) oxidation hardly affected the production of CO 2 , but specifically suppressed the decomposition of lignin. Kramer et al (2012) reported that the oxidized lignin content increased with increasing SRO mineral content by studying a chronosequence of volcanic soils in Hawai'i.…”
Section: Effect Of Feo On Soil Organic Carbon Chemical Structuresupporting
confidence: 92%
“…and biologically mediated gases (Hall and Silver, 2015;Hall et al, 2016), and of biogeochemical processes that cross wide spatial and temporal scales, i.e., what we are accustomed to calling ecological and geological timescales (e.g., Shanley et al, 2011;Dialynas et al, 2016). The research demonstrates how lithologic knickpoints that cross streams and resist downcutting control up-catchment soil formation, plant productivity, and landscape evolution (Wolf et al, 2016).…”
Section: Colocating Ilters and Czosmentioning
confidence: 94%